The Primal Archetypal and Mythical Crone in Toni Morrison’s Portrayals of the Elder Woman - Manuela López-Ramírez (Feminismo/s, 2022)
Morrison’s portrayals of the elderly woman resonate with images of the wise mythical Crone, a universal image embedded in our consciousness. In pre-patriarchal societies, elder women, Crones, were associated with both life and death. The advent of patriarchy changed how aging females were perceived and their societal roles. They were diabolized, disempowered, and regarded as useless and invisible. However, Morrison’s Crones are strong life forces, and an active valuable part of their communities. Morrison revalues their traditional maternal domestic roles, and motherhood and household become, respectively, a transgressive act and a site of resistance and power. With their ancestral spiritual/supernatural/healing properties, her Crones are ancestor figures and moral beacons for their communities. In her oeuvre, Morrison reassesses and reclaims the primordial pre-patriarchal crone archetype to empower and honor old black women and their contributions to the black community.